Experiment and simulation of launching process of a small-diameter steel cartridge case - Han-dong Zhao (Defence Technology, 2014)
In order to explore the rules of the deformation force during the launching of a small-diameter steel cartridge, the semi-closed bomb test method is used to test the greatest strains on chamber outer wall under the different chamber pressures. The pressure curves of cartridge chamber are measured in experiment, and the tensile test data of cartridge are loaded into the numerical calculation to compare with the experimental data. The conclusion was obtained that the calculated results match better with the experimental results by considering strain rate bilinear kinematic hardening material constitutive model. The forces on the various parts of the cartridge during launching and their deformation rules are achieved, in which the equivalent plastic strain decreases and the cylinder ring withstands the maximum equivalent stress when the cartridge case clings to the bore from the mouth to the bottom.